Circadian Rhythm Protein Bmal1 Modulates Cartilage Gene Expression in Temporomandibular Joint Osteoarthritis via the MAPK/ERK Pathway - Chen, Guokun; Zhao, Haoming; Ma, Shixing; Chen, Lei; Wu, Gaoyi; Zhu, Yong; Zhu, Jie; Ma, Chuan; Zhao, Huaqiang (Frontiers in Pharmacology, 2020)
The purpose of this study was to elucidate the role of the circadian gene Bmal1 in human cartilage and its crosstalk with the MAPK/ERK signaling pathway in temporomandibular joint osteoarthritis (TMJ-OA). We verified the periodical variation of the circadian gene Bmal1 and then established a modified multiple platform method (MMPM) to induce circadian rhythm disturbance leading to TMJ-OA. IL-6, p-ERK and Bmal1 mRNA and protein expression levels were assessed by real-time RT-PCR and immunohistochemistry. Chondrocytes were treated with an ERK inhibitor (U0126), siRNA and plasmid targeting Bmal1 under IL-6 simulation; then, the cells were subjected to Western blotting to analyze the relationship between Bmal1 and the MAPK/ERK pathway. We found that sleep rhythm disturbance can downregulate the circadian gene BMAL-1 and improve phosphorylated ERK (p-ERK) and IL-6 levels. Furthermore, Bmal1 siRNA transfection was sufficient to improve the p-ERK level and aggravate OA-like gene expression changes under IL-6 stimulation. Bmal1 overexpression relieved the alterations induced by IL-6, which was consistent with the effect of U0126 (an ERK inhibitor). However, we also found that BMAL1 upregulation can decrease ERK phosphorylation, whereas ERK downregulation did not change BMAL1 expression. Collectively, this study provides new insight into the regulatory mechanism that links chondrocyte BMAL1 to cartilage maintenance and repair in TMJ-OA via the MAPK/ERK pathway and suggests that circadian rhythm disruption is a risk factor for TMJ-OA.